Effect of indigenous Lactobacillus rhamnosus isolated from bovine milk on microbiological characteristics and aromatic profile of traditional yogurt. (March 2016) - Innocente, Nadia; Biasutti, Marialuisa; Rita, Frisina; Brichese, Romina; Comi, Giuseppe; Iacumin, Lucilla
Abstract: The indigenous Lactobacillus rhamnosus DSA LR1 was isolated from milk that was obtained from a restricted geographical area in northeast Italy and it was chosen, among other isolated strains on the bases of its resistance to the pH of gastric juices, the bile salts, the antibiotics and its lipolytic and proteolytic activities. The indigenous isolated potential probiotic bacteria were then added in combination with starter bacteria to the milk used for yogurt production. The results showed that L. rhamnosus DSA LR1 was able to maintain its viability for the entire shelf-life period without affecting on the viability or acidification capacity of starter culture. At the end of the fermentation period, the yogurt that had been co-fermented with L. rhamnosus DSA LR1 presented an aroma profile that was qualitatively similar to the control yogurt but less intense from a quantitative point of view. However, all of the major volatile compounds tended to increase during storage at 4 °C for 20 days, yogurt with L. rhamnosus had absolute areas larger than the areas of the control yogurt for all major carbonyl compounds. Highlights: The indigenous isolated Lactobacillus rhamnosus DSA LR1 were employed in combination with yogurt starter cultures. Results suggested no obvious interference of probiotic bacteria on the growth and viability of starters. L. rhamnosus DSA LR1 allowed us to obtain a functional product characterized by a rich flavour profile.